Modafinil potentiates cocaine self-administration by a dopamine-independent mechanism: possible involvement of gap junctions - Mereu, Maddalena (Neuropsychopharmacology, 2020)
Modafinil and methylphenidate are medications that inhibit the neuronal reuptake of dopamine, a mechanism shared with cocaine. Their use as “smart drugs” by healthy subjects poses health concerns and requires investigation. We show that methylphenidate, but not modafinil, maintained intravenous self-administration in Sprague-Dawley rats similar to cocaine. Both modafinil and methylphenidate pretreatments potentiated cocaine self-administration. Cocaine, at self-administered doses, stimulated mesolimbic dopamine levels. This effect was potentiated by methylphenidate, but not by modafinil pretreatments, indicating dopamine-dependent actions for methylphenidate, but not modafinil. Modafinil is known to facilitate electrotonic neuronal coupling by actions on gap junctions. Carbenoxolone, a gap junction inhibitor, antagonized modafinil, but not methylphenidate potentiation of cocaine self-administration. Our results indicate that modafinil shares mechanisms with cocaine and methylphenidate but has a unique pharmacological profile that includes facilitation of electrotonic coupling and lower abuse liability, which may be exploited in future therapeutic drug design for cocaine use disorder.